PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSONAL BRANDING TUPPERWARE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI KOTA BATAM - Angeline, Angeline; Purba, Tiurniari (LPPM Universitas Putera Batam, 2025)
This research is quantitative research which aims to find out of product quality, brand image and personal branding of Tupperware on consumer purchasing decisions in Indonesia. The analysis in this research uses an explanatory approach. The sampling technique used a sampling snowball, the sample consisted of 100 respondents who had purchased Tupperware. The analytical method used in this research is multiple linear regression analysis. This research is motivated by the problem of lack of marketing for Tupperware products which has resulted in these products currently experiencing a drastic decline in consumers. This research is research and development. Research was conducted on people in Batam City who had purchased or used Tupperware products.